Burden of new hospitalization for heart failure: a population‐based investigation from Italy. (7th May 2014) - Corrao, Giovanni; Ghirardi, Arianna; Ibrahim, Buthaina; Merlino, Luca; Maggioni, Aldo Pietro
<x xml:space="preserve">Abstract</x> Aims Heart failure has been described as one of the emerging pandemics of the 21st century. This report aims to measure the burden of new hospitalization for heart failure in the population of an Italian region of nearly 10 million inhabitants. Methods and results Data were retrieved from healthcare utilization databases covering the population of the Italian region of Lombardy. We identified patients who were hospitalized for the first time with a primary diagnosis of heart failure (hospitalized heart failure, HHF) during 2011. Incident HHF cases were used for measuring incidence rates and exploring mortality, re‐hospitalizations, and healthcare costs on the 1‐year time horizon after the index hospitalization. Out‐of‐hospital mortality, hospitalizations, and healthcare costs were also measured in a referent cohort free from heart failure hospitalization and matched 1:1 by gender and age with the HHF cohort. The overall HHF incidence rate was 32 and 20 events per 10 000 person‐years in men and women, respectively. The incidence increased steeply with age in both genders. Among newly hospitalized patients, 7% died during hospitalization. Among survivors, cumulative out‐of‐hospital mortality and hospital readmission were 24% and 59%, respectively. The average per capita cost was €11 000, the main cost being hospitalizations. Mortality, readmissions, and costs experienced by HHF patients of 88, 75, and 79%, respectively, exceeded those of the referent cohort. Conclusions The main burden associated with HHF is related to hospitalizations. Effective treatment options that decrease hospitalization rates could reduce patients' suffering and offer considerable cost savings.